Apakah Anda Merasa Kesepian ? Eksplorasi Kepribadian dan Kualitas Pertemanan pada Remaja - Fikrie Fikrie; Ceria Hermina; Lita Ariani (Faculty of Ushuluddin and Humanities, 2021)
This study examined the role of hardiness, friendship quality, and loneliness on first-year college students. 333 participants completed three scales: hardiness scale, friendship quality scale, and loneliness scale. A multiple linear regression test was used with hardiness and friendship quality as an independent variable and loneliness as a dependent variable. The result showed that hardiness and friendship quality simultaneously were significant predictors of loneliness (F = 101,03; p <,001). Loneliness variance was explained by both hardiness and friendship quality of 38% (R2 =,38). When given separately, hardiness was significant predictor to loneliness with variance explained of 26,22% (R2 = ,2622 ; p < ,001) and friendship quality was significant predictor to loneliness with variance explained of 11,25% (R2 = ,1125 ; p < ,001). It can be concluded that improving the hardiness and friendship quality of the first-year college students will lead them to reduce loneliness.